BUSANA MUSLIM UNTUK GENERASI ALPHA PADA EVENT JAKARTA MUSLIM FASHION WEEK 2021/2022 - Nyoman Ayu Permata Dewi; I Gusti Ayu Agung Mia Darmiati; Kadek Ayu Dwi Ratri Pradnyandari (Narada : Jurnal Desain dan Seni, 2021)
Muslim clothing has provisions for Muslim clothing in accordance with Islamic law, so that designing Muslim clothing cannot be separated from these regulations. This brings a challenge for fashion designers, to develop Muslim fashion designs that follow fashion trends but still adhere to the rules of Islamic law. The Jakarta Muslim Fashion Week 2021/2022 event is an event that accommodates fashion designers to develop their abilities in Muslim fashion in Indonesia. One of the works at the event was inspired by a concept, namely, the alpha generation. The alpha generation is the latest generation created by Mark McCrindle, for children born in 2010-2025. It is predicted that this generation has different characteristics from the previous generation. This discovery was then used as inspiration in the creation of women's Muslim clothing, to welcome the alpha generation based on the predicted characteristics of the alpha generation.The research on this work uses the method of observation, literature study and exploration. The observation method is carried out on the object of research which is a concept in the creation of works, namely the alpha generation. The literature study method collects data through various sources related to research. Meanwhile, in the exploration method, researchers conducted an in-depth exploration of the definition and character of the alpha generation. Based on the results of research on the concept of alpha generation, several data were generated which were summarized into a mind map, then selected a few words as keywords and made a moodboard. Based on the moodboard, alternative designs were designed and produced 6 ready-to-wear Muslim fashion designs with urban, modern, futuristic and comfortable styles. Of the 6 alternative designs, only 2 designs were selected for later realization. Both clothes are made with materials that have been adapted to the characteristics of the alpha generation who are open-minded, creative, adaptable, optimistic and high mobility.